2016
DOI: 10.1016/j.trre.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Combined heart–liver transplantation: Indications, outcomes and current experience

Abstract: Combined heart–liver transplantation is a rare, life-saving procedure that treats complex and often fatal diseases including familial amyloidosis polyneuropathy and late stage congenital heart disease status-post previous repair. There were 159 combined heart–liver transplantations performed between January 1, 1988 and October 3, 2014 in the United States. A multitude of potential techniques to be used for combined heart and liver transplant including: orthotopic heart transplant (OHT) and orthotopic liver tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 52 publications
0
41
0
1
Order By: Relevance
“…20 The most common indications for CHLT are familial amyloidosis and heart failure associated with cardiac cirrhosis. 18,19,21 Other recipient pathologies include metabolic diseases, alcoholism, primary end-stage cirrhosis associated with cardiomyopathy, and heart failure resulting in liver cirrhosis. 18 Atluri et al described their protocol when patients are being considered for heart transplantation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…20 The most common indications for CHLT are familial amyloidosis and heart failure associated with cardiac cirrhosis. 18,19,21 Other recipient pathologies include metabolic diseases, alcoholism, primary end-stage cirrhosis associated with cardiomyopathy, and heart failure resulting in liver cirrhosis. 18 Atluri et al described their protocol when patients are being considered for heart transplantation.…”
mentioning
confidence: 99%
“…The incidence of acute cardiac rejection also was lower in the CHLT group than in those who underwent cardiac transplantation alone (8.9% v 23.9%, p ¼ 0.002). 17,[21][22][23] The liver appears to offer protection against rejection by other organs when the liver is part of a multiorgan transplantation procedure. There is growing evidence that acute cardiac rejection and cardiac allograft vasculopathy are less common after CHLT.…”
mentioning
confidence: 99%
“…As the majority of CHLT candidates with severe cardiac insufficiency are unable to tolerate the hemodynamic changes that occur during liver transplantation, it is suggested that heart transplantation be performed prior to liver transplantation [ 11 ]. A number of operative strategies have been published, including (1) a separate staged operation involving heart transplantation followed by liver transplantation, (2) heart transplantation on CPB then liver transplantation after discontinuing CPB during the same operation, and (3) heart and liver transplantation both performed on CPB [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of operative strategies have been published, including (1) a separate staged operation involving heart transplantation followed by liver transplantation, (2) heart transplantation on CPB then liver transplantation after discontinuing CPB during the same operation, and (3) heart and liver transplantation both performed on CPB [ 3 ]. The most widely applied technique is performing the heart transplant on CPB, separating from the bypass, and continuing the liver transplant with selective use of venovenous bypass [ 10 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…). The current literature of CHLT outcomes is limited by small sample size and single‐center experiences …”
Section: Introductionmentioning
confidence: 99%